Implementation of an ecohealth approach for better management of leptospirosis in Kulon Progo District, Yogyakarta Special Province, Indonesia - Widiasih, D.A.; Artama, W.T.; Sumiarto, B.; Husodo, A.; Kutanegara, P.M.; Mulyani, G.; Widodo, E.; Fihiruddin; Purwantoro, A.; Santosa, K.A.; Djohan, T.S.; Sancoko, H.; et al. (Veterinary Public Health Centre for Asia Pacific, 2013)
Outbreaks of leptospirosis in Yogyakarta Special Province, Indonesia cause serious problems in humans and animals. With case fatality rates for the Kulon Progo District, Yogyakarta Special Province of 5.8% for 2011, 7.1% for 2012 and 33.3% for 2013 the PH importance has been clearly demonstrated. High mortalities in human due to renal failure can be observed whereas in animals a loss of production (i.e. due to abortions) is most prominent. The observed re-emergence of leptospirosis seems to be caused by multifactor components, and highly linked to environmental factors. However, observed cases of leptospirosis and related health impacts need to be better understood. Classical sector specific approaches have failed to be effective. Thus a more successful control and prevention requires alternative concepts such as EcoHealth to ensure transdisciplinary and participatory approaches across sectoral barriers. The objective of this study is to explore potential risk factors for leptospirosis in human and animals by using qualitative and quantitative tools for data collection. In-depth interviews (IDI) targeted on knowledge of zoonotic diseases particularly leptospirosis and behavior of people. Focus group discussions (FGD) were performed and included farmers, village officials, and stakeholders from Municipal Health Services and Livestock Services. The survey was carried out in between April to May 2013 in selected communities (N=9) of Kulon Progo with high (N=3), medium (N=3) and low cases (N=3) of human leptospirosis based on a recent serological survey. It is anticipated that the results from the FGD and IDI will provide additional information to the first phase of the project (Oct 2011 – May 2012) which focused on quantitative data collection such as prevalence surveys for leptospirosis in animals, questionnaires and spatial analysis using GIS including veterinarians, physicians, ecologists, demographist, social sciences, others stakeholders (government and public sector). Key results from both phases will be presented and synthesized. The synthesis from the qualitative and quantitative surveys will contribute to a better integrated understanding of disease emergence and the basis for a more effective addressing of public health policy concerns in order to better management the disease.